Philosophy of Ki Hajar Dewantara’s Concepts and Independent Learning Curriculum for Indonesian Education Character Building - Nurul Faizah; Ghasa Faraasyatul 'Alam; Nursa'adat Afifah binti Mohamad (Fahima, 2026)
Education is a learning process to develop students without force, but students can develop themselves if they feel free physically and mentally. The Independent Curriculum is a national education policy that emphasizes student-centered learning and character building. However, this curriculum is often understood merely as a response to the demands of the times, without being studied in depth from the perspective of the philosophical foundations of national education. On the other hand, Ki Hajar Dewantara’s thinking places character education, responsible freedom of learning, and education without coercion at the core of the educational process. This study aims to analyze the relevance of Ki Hajar Dewantara’s educational thinking to the Independent Curriculum in the framework of character education in higher education. This study used a literature review method with a conceptual-philosophical approach, with primary sources in the form of Ki Hajar Dewantara’s works and official documents of the Independent Curriculum, as well as secondary sources from relevant scientific literature. The results of the study showed that Ki Hajar Dewantara’s educational principles are strongly aligned with the direction and spirit of the Independent Curriculum. The Independent Curriculum can be understood as the actualization of Ki Hajar Dewantara’s educational values in contemporary educational policy.